MiRNAs from serum-derived extracellular vesicles as biomarkers for uveal melanoma progression - Wróblewska, Joanna Patrycja; Lach, Michał Stefan; Rucinski, Marcin; Piotrowski, Igor; Galus, Lukasz; Suchorska, Wiktoria Maria; Kreis, Stephanie; Marszałek, Andrzej (Frontiers in Cell and Developmental Biology, 2022)
Uveal melanoma (UM) is a rare type of malignancy that originates from melanocytes in the choroid, iris and the eye’s ciliary body. Biomarkers for early detection and progression of UM, especially the molecular traits governing the development of metastasis, are still not available in clinical practice. One extensively studied components of liquid biopsies are extracellular vesicles. Due to their unique molecular cargo, they can contribute to early cancer development and at the same time carry markers for disease onset and progression. For characterisation of the miRNA profiles present in circulating serum-derived exosomes of patients with diagnosed primary and metastatic UM, we have analyzed the miRNA cargos using next-generation sequencing followed by RT-qPCR validation in a cohort of patients (control n = 20; primary n = 9; metastatic n = 11). Nine miRNAs differentiating these patient groups have been established. We show that hsa-miR-144-5p and hsa-miR-191-5p are the most promising biomarker candidates, allowing the categorization of patients into local and advanced UM. Additionally, the comparison of miRNA expression levels in exosomes derived from UM patients with those derived from healthy donors revealed that hsa-miR-191-5p, -223-3p, -483-5p, -203a has the potential to be used as an early marker for the presence of UM. This pilot study reveals that miRNAs extracted from circulating exosomes could be exploited as potential biomarkers in UM diagnosis and, more importantly, for indicating metastatic spread.